Transcriptomic responses to transportation stress in the juvenile Chinese sea bass (Lateolabrax maculatus) - Yue Su; Sarinpan Kokau; Xiao-Ning Zhang; Yun-Wei Dong (Aquaculture Reports)
Transportation is a necessary aspect of the aquaculture industry that might induce inevitable stress and compromise product quality. In the present study, the transcriptomic profiles in the brain and liver of Chinese sea bass (Lateolabrax maculatus) were characterized after transportation stress at two different densities (low-density: 20 kg/m3 and high-density: 40 kg/m3). Transcriptome analysis revealed that 485 and 627 differentially expressed genes (DEGs) were determined in the brain and liver from sea bass after transportation stress, respectively. KEGG enrichment analysis demonstrated that the DEGs were significantly enriched in focal adhesion, PI3K-Akt, MAPK signaling pathway, apoptosis, and circadian rhythm under transportation stress. Protein-Protein Interaction (PPI) networks showed that COL1A1, COL1A2, COL5A2, COL10A1, and COL16A1 associated with protein digestion and absorption, together with LUM, SERPINH1, and ADAMTS2 were recognized as hub genes in the brain, while JUN, NFKB1, MAPK14, MAP3K7, HSPA1, HSP90AA1, PIK3CA and PIK3R1 tightly related to MAPK and PI3K-Akt signaling pathway and SMAD3 and PPARGC1A were considered as hub genes in the liver. These results indicated that the alterations in transcripts of sea bass are primarily involved in cell adhesion, signal transduction, immune response, and metabolic regulation in response to transportation stress. Our study provides new perspectives into the molecular mechanism underlying responses to transportation and theoretical support for optimizing transportation in the Chinese sea bass.